The relationship between the diet, microelements, macronutrients and vitamins on the schizophrenia – literature analysis - Kozyra, Magdalena; Klas, Jakub; Szabat, Marta; Samoń-Drzewicka, Anna Maria; Milanowska, Joanna (Journal of Education, Health and Sport, 2020)
Introduction: Schizophrenia is a disease that affects approximately 1% of the population. It begins in adult humans. It turns out that there are factors that predispose to schizophrenia, and by modifying your lifestyle, you can reduce the likelihood of its occurrence. One of such factors is the diet and microelements, macronutrients and vitamins that we consume every day. The aim of the study: The aim of this study was to find out the relationship between the diet, microelements, macronutrients, vitamins and the schizophrenia disease. Material and method: The research of articles was done in the websites such as PubMed and Google Scholar. Description of the state of knowledge: Ketogenic and gluten-free diet are promising tools in decreasing the symptoms of and treating schizophrenia. Micro- and macroelement imbalances are present in schizophrenic patients, but their correlation with development of schizophrenia is not clear. Folate, vitamin D and vitamin B12 supplementation could prove useful in the treatment. Summary: There are many studies that try to combine the implications of a balanced diet and the proper supply of elements and their impact on schizophrenia's occurence and symptomology. Still, futher investigation of these topics is needed to provide the most suitable guidelines and applications of proper nutrition of schizophrenic patients.